The Influence of the Preaching Approach on The Millennial Generation in Jaya District, Aceh Jaya Regency - Nurul FITDARI; Khairul HABIBI; Fakhruddin FAKHRUDDIN (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
This study aims to determine the effect of the da'wah approach on the millennial generation in Jaya District, Aceh Jaya Regency. This study is a field study with a quantitative approach and descriptive design. The population in this study is the millennial generation in Jaya District, Aceh Jaya Regency, with a total of 100 respondents. The sample in this study was determined using an accidental sampling technique. Data collection was carried out through a closed questionnaire, and the data were analyzed using a simple linear regression method with the help of the SPSS version 25 program. The results showed that the da'wah approach has a positive and significant influence on the millennial generation, with a regression coefficient value of 0.414 and a significance level of 0.000 (<0.05). The determination value (R²) of 0.254 indicates that 25.4% of the variation in the behavior of the millennial generation can be explained by the da'wah approach, while the rest is influenced by other factors. Thus, it can be concluded that the da'wah approach has a significant influence on the behavior of the millennial generation.